Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

First report of Halophila stipulacea (Forsskål) Ascherson,1867 in the Dominican Republic, an invasive species that continues to expand across the Caribbean - Yira Rodríguez-Jerez; Rita Sellares-Blasco; Maria F. Villalpando; Estefany Vargas-Pérez; Andreina Valdez-Trinidad; Someira Zambrano; Yasmin D. Evangelista; Sergio D. Guendulain-García; Aldo Croquer (Aquatic Botany, 2025)

Effects of elevated temperatures and health status of the crustose coralline algae Hydrolithon boergesenii (Corallinales: Mastophoroideae) on the larval settlement of Diploria labyrinthiformis (Scleractinia: Faviinae) - Rita I. Sellares-Blasco; Nepsis García; Maria F. Villalpando; Iván Cano; Aldo Croquer (Regional Studies in Marine Science, 2023)

Planning for resilience: Incorporating scenario and model uncertainty and trade‐offs when prioritizing management of climate refugia - Iliana Chollett; Ximena Escovar‐Fadul; Steven R. Schill; Aldo Croquer; Adele M. Dixon; Maria Beger; Elizabeth Shaver; Valerie Pietsch McNulty; Nicholas H. Wolff (Global Change Biology, 2022)
Climate change has become the greatest threat to the world's ecosystems. Locating and managing areas that contribute to the survival of key species under climate change is critical for the persistence of ecosystems in the future. Here, we identify ‘Climate Priority’ sites as coral reefs exposed to relatively low levels of climate stress that will be more likely to persist in the future. We present the first analysis of uncertainty in climate change scenarios and models, along with multiple objectives, in a marine spatial planning exercise and offer a comprehensive approach to incorporating uncertainty and trade‐offs in any ecosystem. We first described each site using environmental characteristics that are associated with a higher chance of persistence (larval connectivity, hurricane influence, and acute and chronic temperature conditions in the past and the future). Future temperature increases were assessed using downscaled data under four different climate scenarios (SSP1 2.6, SSP2 4.5, SSP3 7.0 and SSP5 8.5) and 57 model runs. We then prioritized sites for intervention (conservation, improved management or restoration) using robust decision‐making approaches that select sites that will have a benign climate under most climate scenarios and models. The modelling work is novel because it solves two important issues. (1) It considers trade‐offs between multiple planning objectives explicitly through Pareto analyses and (2) It makes use of all the uncertainty around future climate change. Priority intervention sites identified by the model were verified and refined through local stakeholder engagement including assessments of local threats, ecological conditions and government priorities. The workflow is presented for the Insular Caribbean and Florida, and at the national level for Cuba, Jamaica, Dominican Republic and Haiti. Our approach allows managers to consider uncertainty and multiple objectives for climate‐smart spatial management in coral reefs or any ecosystem across the globe.

Site Selection for Coral Reef Restoration Using Airborne Imaging Spectroscopy - Steven R. Schill; Gregory P. Asner; Valerie Pietsch McNulty; F. Joseph Pollock; Aldo Croquer; Nicholas R. Vaughn; Ximena Escovar-Fadul; George Raber; Elizabeth Shaver (Frontiers in Marine Science, 2021)
Over the past decade, coral restoration efforts have increased as reefs continue to decline at unprecedented rates. Identifying suitable coral outplanting locations to maximize coral survival continues to be one of the biggest challenges for restoration practitioners. Here, we demonstrate methods of using derivatives from imaging spectroscopy from the Global Airborne Observatory (GAO) to identify suitable coral outplant sites and report on the survival rates of restored coral at those sites. Outplant sites for a community-based, citizen science outplant event in Bávaro, Dominican Republic, were identified using expert-defined criteria applied to a suitability model from data layers derived from airborne imagery. Photo quadrat analysis of the benthic community confirmed the accuracy of airborne remote sensing maps with live coral cover averaging 3.5–4% and mean algal cover (macro algae and turf) ranging from 28 to 32%. Coral outplant sites were selected at 3–7 m depth with maximized levels of habitat complexity (i.e., rugosity) and live coral cover and minimized levels of macroalgal cover, as predicted by the imaging spectrometer data. In November 2019, 1,722 Acropora cervicornis fragments (80–180 mm in length) were outplanted to these sites. Surveys conducted in January 2020 in four of these sites confirmed that 92% of outplants survived after 3 months. By October 2020 (11 months after outplanting), survivorship remained above 76%. These results demonstrate higher than average success rates for coral outplant survival for this species. An online tool was developed to enable replication and facilitate future selection of coral restoration sites. Our objective is to present a case study that uses GAO-derived map products within a suitability model framework to provide a quantitative and replicable method for selecting coral restoration sites with the goal of increasing outplant survival over time.

Assisted Coral Reproduction in the Dominican Republic: A Successful Story to Replicate in the Caribbean - Rita I. Sellares-Blasco; Maria F. Villalpando; Sergio D. Guendulain-García; Aldo Croquer (Frontiers in Marine Science, 2021)
Coral assisted fertilization, larval rearing and recruit propagation success in significant ecological scales, largely depend on scaling up and replicating these efforts in as many regions as possible. The Dominican Foundation for Marine Studies (FUNDEMAR) has become a pioneer of these efforts in the Dominican Republic, being the first institution to successfully implement coral sexual reproduction techniques in the country and establishing the first mobile larvae culturing facility. Here we share our perspective on three main components behind the success of FUNDEMAR’s program: (1) a self-sustainable program in alliance with local and international organizations, (2) the design and construction of the first Coral Assisted Reproduction Laboratory in the country, and a (3) clearly defined scalable structure for outcome performance. Two years after program implementation, FUNDEMAR has successfully produced an annual regional coral spawning prediction calendar, cultured seven coral species, and seeded over 4,500 substrates with more than 268,200 sexual coral recruits in approximately 1,880 m 2 reef areas. Here, we provide a detailed description of a fully functional assisted coral reproduction program, including the lessons learned during its implementation as well as a series of specific solutions. We hope this work will help and inspire other countries and small institutions to replicate FUNDEMAR’s coral assisted reproduction program components and contribute to the expansion of sexual coral restoration efforts in the Caribbean.